Komunikasi Ritual Dalam Proses Pelaksanaan Tradisi Meameng-Ameng pada Umat Hindu Krama Pura Gumang di Dusun Peninjoan Narmada - Kadek Mira Widya Sari; I Wayan Ardhi Wirawan; Dewi Kusumasanthi (IAHN Gde Pudja Mataram, 2026)
Ritual communication serves as a medium through which religious values, meanings, and beliefs are transmitted and maintained across generations, forming an integral part of a community’s cultural heritage. This study examines the implementation of ritual communication in the Meameng-ameng tradition practiced by the Hindu community of Pura Gumang in Peninjoan Hamlet, Narmada District, West Lombok. A qualitative descriptive method was employed to explore and describe the stages of the tradition and their communicative significance.The findings indicate that ritual communication in the Meameng-ameng tradition is expressed through two main stages: Ngadegang and Ngelukar. The Ngadegang stage involves preparatory activities, including ngeringgit performed by male participants and metanding (the preparation of ritual offerings) carried out by female participants, followed by the Melasti purification ceremony. The Ngelukar stage is characterized by the gathering of four jempana, symbolizing kinship, unity, and harmony within the community. The ritual continues with the Purwa Daksina ceremony at Pura Gumang and Segara Pengayat, utilizing offerings prepared by the sarati banten. The study shows that the Meameng-ameng tradition functions as an effective medium for conveying religious, social, and cultural values while reinforcing the collective identity of the Hindu community in Peninjoan Hamlet. These findings contribute to the development of ritual communication studies in religious and cultural contexts and support the preservation of local wisdom amid contemporary social change.